Are air travellers willing to pay for reducing or offsetting carbon emissions? Evidence from Italy. (December 2020) - Rotaris, Lucia; Giansoldati, Marco; Scorrano, Mariangela
Highlights: The WTP ranges between €12 and €38 per ton and between €14 and €66 per flight. It is higher for projects aimed at forest protection, afforestation, reforestation. It is significantly lower if the description of the project financed is missing. Gender, occupational status and education degree influence the WTP. Also travel habits and environmental consciousness influence the WTP. Abstract: The aviation industry is one of the fastest-growing sectors in producing carbon emissions. In order to reduce its carbon footprint and to respond to the increasing number of people concerned about the impact caused by air transport on climate change, the International Civil Aviation Organization (ICAO) has recently passed the "carbon neutral growth from 2020" resolution requiring that the global net CO2 emissions from international aviation do not exceed the 2019–2020 levels. Airlines, however, can act beyond their obligations under the ICAO resolution investing in projects aimed at reducing or offsetting all the emissions produced not only by their international flights but also by their domestic flights. The aim of this paper is to test whether Italian air travellers would be willing to donate a contribution to finance these projects and whether the willingness to pay depends on the projects' type and on the projects' effectiveness. To this aim we performed a stated-choice experiment involving a sample of 1228 Italians who travelled by plane at least once in the last 3 years. We find that their willingness to pay ranges from €12 to €38 per ton and from €14 to €66 per flight. The description of the project type to be financed via the passengers' donations is one of the most important factors influencing their willingness to pay. Other key factors are the quantity of CO2 reduced or offset via the project and the respondents' gender, education degree, occupational status, environmental consciousness and travel habits. Our results are useful for airlines to design the donation proposals and improve the corporate image and for policy makers to support air travellers' environmental conscious behaviour and airlines' environmental sustainable strategies.